PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA PADA PT. TOYOTA ASTRA MOTOR - Yeni, Fitri (Jurnal Ekobistek, 2014)
This research aim for PT. Toyota Astra Motor to know how much the influences of Brand Image and Promotion simultsneously and partialy in  Purchasing Decision.  The method of data collection used is  in the form of questionnaire. The analysis methods used are simple linear regression analysis and multiple linear regression analysis.   Based on the Partial Test (Test t) test results of the regression coefficient, Brand Image has t count > t table (3,919>1,990) which means there is a significant influences between Brand Image and Purchasing Decisions. Promotion has a t count > t table (5,190>1,990), which means there is a significant influences between Promotion and Purchasing Decisions. Then, based on simultaneous test (Test F) can be determined F count  value 557,229 > F table  value of 2,71 which means the variable Brand Image, and Promotion significantly influence the Purchasing Decisions variables. And based on koefisien test determination (R2) the value is 0,942. it indicates  the persentage of the contribution variable Brand Image, and Promotion to ward Purchasing Decisions is at 94,2%. the residue is 6,8% influenced by other variables which is not included in the studied variables. Keywords: Purchasing Decisions, Brand Image, and Promotion